Analisis Eksplanatori Determinan Citra Merek Ramah Lingkungan: Peran Nilai Ekosentris, Otoritas Hijau, Konsistensi Operasional Ekologis, Dan Koherensi Identitas Berkelanjutan - Haris Murwanto Paramitayana; Yeremia Wijayanto Yeremia; Aprih Santoso Aprih (Community Engagement and Emergence Journal (CEEJ), 2026)
Background: Rising environmental awareness pushes firms to build green brand image, yet many suffer gaps between claims and reality. This study examines the effects of Ecosentris Values, Green Authority, Ecological Operational Consistency, and Sustainable Identity Coherence on Green Brand Image. Methods: Quantitative causal-explanatory design with 100 randomly selected consumers. Data processed via SPSS within a SEM-PLS framework to assess measurement and structural models. Results: All four variables exert positive significant effects: Ecosentris Values (β=0.168; p=0.041), Green Authority (β=0.215; p=0.006), Ecological Operational Consistency (β=0.194; p=0.016), and Sustainable Identity Coherence (β=0.342; p=0.000). The model explains 62.8% of variance in green brand image. Conclusion: Green brand image emerges from synergy among foundational values, competence trust, behavioral alignment, and unified identity. Sustainable identity coherence is the strongest predictor, indicating holistic alignment matters more than partial efforts.